2017
DOI: 10.54386/jam.v19i1.762
|View full text |Cite
|
Sign up to set email alerts
|

Impact of weather parameters on population dynamics of oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) under south Gujarat mango ecosystem

Abstract: The field experiment was conducted during 2013-16 at Navsari Agricultural University, Paria, Gujarat to study the role of weather parameters on population dynamics of oriental fruit fly, Bactrocera dorsalis on mango, Mangifera indica L. Fruit flies were recorded throughout the investigation period, wherein maximum catches were observed during April - July which coincided with fruiting and harvesting stages of the crop. Weather parameters viz., minimum temperature, evening relative humidity, rainfall and wind v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…These findings are very much in agreement with a study conducted on fruitflies infesting sweet oranges in Zimbabwe, 20 where also statistically significant correlationswerefound between the fruit fly population and meteorological parameters of relative humidity and mean temperature. The observation is also in agreement with the findings in mango, 27,20 where the population of fruit flies was directly correlated with temperature, humidity and rainfall. But the wind speed, in the current study, is not show a statistically significant correlation with flies per trap (Table 1), which may be due to undulated topography where wind speed is generally not appreciable and does not show much seasonal or monthly variation.…”
Section: Relationships Between the Weather Variables And Population D...supporting
confidence: 92%
See 3 more Smart Citations
“…These findings are very much in agreement with a study conducted on fruitflies infesting sweet oranges in Zimbabwe, 20 where also statistically significant correlationswerefound between the fruit fly population and meteorological parameters of relative humidity and mean temperature. The observation is also in agreement with the findings in mango, 27,20 where the population of fruit flies was directly correlated with temperature, humidity and rainfall. But the wind speed, in the current study, is not show a statistically significant correlation with flies per trap (Table 1), which may be due to undulated topography where wind speed is generally not appreciable and does not show much seasonal or monthly variation.…”
Section: Relationships Between the Weather Variables And Population D...supporting
confidence: 92%
“…During the study period, it was found that the mean number of males trapped varied from 0. 20 and similar work done on mango, 31,27 where the highest population were found in the near ripening and ripening stage of the fruits.…”
Section: Methodsmentioning
confidence: 53%
See 2 more Smart Citations
“…In subtropical regions of Pakistan the temperature fluctuates in regular intervals which mostly favour the fruit fly population to increase. So, this study might be helpful to manipulate the fruit fly population by understanding the correlation between fruit fly population and temperature with humidity [30][31][32]. It has been noted that with the change in abiotic factors like temperature and humidity a fluctuation in population dynamics of B. Dorsalis occurs simultaneously.…”
Section: Discussionmentioning
confidence: 99%